Robust quantification of fish early life CO2 sensitivities via serial experimentation - Baumann, Hannes; Cross, Emma L.; Murray, Chris S. (Biology Letters, 2018)
Keywords: dept.egm; peer-reviewed

Diel and tidal pCO2 × O2 fluctuations provide physiological refuge to early life stages of a coastal forage fish - Cross, Emma L.; Murray, Christopher S.; Baumann, Hannes (Scientific Reports, 2019)
Coastal ecosystems experience substantial natural fluctuations in pCO2 and dissolved oxygen (DO) conditions on diel, tidal, seasonal and interannual timescales. Rising carbon dioxide emissions and anthropogenic nutrient input are expected to increase these pCO2 and DO cycles in severity and duration of acidification and hypoxia. How coastal marine organisms respond to natural pCO2 × DO variability and future climate change remains largely unknown. Here, we assess the impact of static and cycling pCO2 × DO conditions of various magnitudes and frequencies on early life survival and growth of an important coastal forage fish, Menidia menidia. Static low DO conditions severely decreased embryo survival, larval survival, time to 50% hatch, size at hatch and post-larval growth rates. Static elevated pCO2 did not affect most response traits, however, a synergistic negative effect did occur on embryo survival under hypoxic conditions (3.0 mg L-1). Cycling pCO2 × DO, however, reduced these negative effects of static conditions on all response traits with the magnitude of fluctuations influencing the extent of this reduction. This indicates that fluctuations in pCO2 and DO may benefit coastal organisms by providing periodic physiological refuge from stressful conditions, which could promote species adaptability to climate change.
Keywords: dept.egm

A 120-year record of resilience to environmental change in brachiopods - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Global Change Biology, 2018)
Keywords: dept.egm; peer-reviewed

Thicker shells compensate extensive dissolution in brachiopods under future ocean acidification - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Environmental Science & Technology, 2019)
Keywords: dept.egm; peer-reviewed